African Swine Fever Virus Structural Protein p17 Inhibits cGAS-STING Signaling Pathway Through Interacting With STING - Zheng, Wanglong; Xia, Nengwen; Zhang, Jiajia; Cao, Qi; Jiang, Sen; Luo, Jia; Wang, Hui; Chen, Nanhua; Zhang, Quan; Meurens, François; Zhu, Jianzhong (Frontiers in Immunology, 2022)
African swine fever virus (ASFV) encodes more than 150 proteins, which establish complex interactions with the host for the benefit of the virus in order to evade the host’s defenses. However, currently, there is still a lack of information regarding the roles of the viral proteins in host cells. Here, our data demonstrated that ASFV structural protein p17 exerts a negative regulatory effect on cGAS-STING signaling pathway and the STING signaling dependent anti-HSV1 and anti-VSV functions. Further, the results indicated that ASFV p17 was located in ER and Golgi apparatus, and interacted with STING. ASFV could interfere the STING to recruit TBK1 and IKKε through its interaction with STING. It was also suggested that the transmembrane domain (amino acids 39–59) of p17 is required for interacting with STING and inhibiting cGAS-STING pathway. Additionally, with the p17 specific siRNA, the ASFV induced IFN-β, ISG 15, ISG 56, IL-6 and IL-8 gene transcriptions were upregulated in ASFV infected primary porcine alveolar macrophages (PAMs). Taken together, ASFV p17 can inhibit the cGAS-STING pathway through its interaction with STING and interference of the recruitment of TBK1 and IKKε. Our work establishes the role of p17 in the immune evasion and thus provides insights on ASFV pathogenesis.